Geomorphological Analysis and Hydrological Potential Zone of Baira River Watershed, Churah in Chamba District of Himachal Pradesh, India - Kuldeep Pareta; Upasana Pareta (Universitas Pendidikan Indonesia, 2017)
In the present study, an attempt has been made to study the quantitative geomorphological analysis and hydrological characterization of 95 micro-watersheds (MWS) of Baira river watershed in Himachal Pradesh, India with an area of 425.25 Km2. First time in the world, total 173 morphometric parameters have been generated in a single watershed using satellite remote sensing data (i.e. IRS-P6 ResourceSAT-1 LISS-III, LandSAT-7 ETM+, and LandSAT-8 PAN OLI merge data), digital elevation models (i.e. IRS-P5 CartoSAT-1 DEM, ASTER DEM data), and soI topographical maps of 1: 50,000 scale. The ninety-five micro-watersheds (MWS) of Baira river watershed have been prioritized through the morphometric analysis of different morphometric parameters (i.e. drainage network, basin geometry, drainage texture analysis, and relief characterizes ). The study has concurrently established the importance of geomorphometry as well as the utility of remote sensing and GIS technology for hydrological characterization of the watershed and there for better resource and environmental managements.